1982
DOI: 10.1111/j.1699-0463.1982.tb00076_90a.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Two Neoplastic Cell Lines (U‐1285 and U‐1568) Derived From Small Cell Carcinoma of the Lung

Abstract: Two human cell lines have been established in vitro from patients with small cell carcinoma of the lung (SCC). The U‐1285 line was derived from the classical small cell type of SCC while the U‐1568 orginated from a larger cell variant. The cell lines grow as suspension cultures and have been passaged continuously in vitro for 3 years (U‐1285) and 2 years (U‐1568), respectively. The malignant nature of the lines is suggested by their infinite growth potential, their capacity to form colonies in agarose and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Total profiling of miRNA in different NSCLC and SCLC cell lines revealed that each cell line expressed ∼100–200 different miRNAs (Figure 1B). For each LC subtype, SCLC and NSCLC, the cell lines were grouped into RS (SF2<0.3) and RR (SF2⩾0.3) on the basis of their clonogenic survival data (Bergh et al , 1982, 1985; Carney et al , 1983; Carmichael et al , 1989; Sirzen et al , 1998). The expression of the different individual miRNAs within each of these cohorts was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total profiling of miRNA in different NSCLC and SCLC cell lines revealed that each cell line expressed ∼100–200 different miRNAs (Figure 1B). For each LC subtype, SCLC and NSCLC, the cell lines were grouped into RS (SF2<0.3) and RR (SF2⩾0.3) on the basis of their clonogenic survival data (Bergh et al , 1982, 1985; Carney et al , 1983; Carmichael et al , 1989; Sirzen et al , 1998). The expression of the different individual miRNAs within each of these cohorts was examined.…”
Section: Resultsmentioning
confidence: 99%
“…The human NSCLC cell lines H23, A549, H157, H661, H1299 and U-1810 and the SCLC cell lines H69, H82, U-1285, U-1690 and U-1906 were used (Bergh et al , 1982, 1985; Carney et al , 1983; Carmichael et al , 1989; Sirzen et al , 1998). All cells were maintained in RPMI 1640 medium (Invitrogen, Stockholm, Sweden) supplemented with 10% of heat-inactivated fetal bovine serum (FBS), ℒ-glutamine (2 mℳ), penicillin (100 U ml −1 ) and streptomycin (100  μ g ml −1 ) (Gibco, Invitrogen, Paisley, UK) at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The fact that cells of As 2 O 3 nonresponding SCLC tumors were larger and that the SCLC-mv cell line (derived from a large cell variant of SCLC; ref. 35) was less sensitive to As 2 O 3 treatment may indicate that the highest efficacy of As 2 O 3 is to be expected in patients with classic small cell type SCLC.…”
Section: Discussionmentioning
confidence: 95%
“…The human SCLC U-1285 (20) and NSCLC U-1810 (21) were kind gifts from Uppsala University where they were established and characterized (22). SCLC H69 and H82, ovarian cancer cell lines A2780 and SKOV-3, foreskin fibroblasts immortalized with hTERT BJ-5ta, bronchial epithelial cells BEAS-2B and hTERT immortalized retina epithelial cells RPE-1 were all purchased from the ATCC.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%